Leptomeningeal amyloidosis: features of the clinical picture (clinical observation) - E. I. Safiulina; O. E. Zinovieva; N. S. Shcheglova; V. V. Rameev; Z. V. Surnina; E. N. Nikitina; O. A. Vorobieva (Неврология, нейропсихиатрия, психосоматика, 2022)
Hereditary transthyretin amyloidosis belongs to a group of diseases with an autosomal dominant type of transmission and a heterogeneous clinical picture, which depends on the type of transthyretin gene mutation. The leptomeningeal form is a rare phenotypic variant of amyloidosis with a predominant involvement of brain and spinal cord meninges, as well as cortical meningeal vessels. The main manifestations of this phenotype include cephalalgic syndrome, episodes of acute cerebrovascular accident, hearing impairment, epileptic seizures, progressive cognitive impairment reaching the degree of dementia, impaired consciousness, etc. The article describes a clinical case of revealing of amyloidogenic mutation Ala45Thr with a hereditary family history and typical manifestations of leptomeningeal amyloidosis at the onset of the disease, as well as impaired renal function. Neuroimaging with contrast enhancement revealed a characteristic thickening of the meninges of the spinal cord due to the deposition of amyloid masses.